Discourse Analysis of Politicians Social Media Posts - Azmi, Alia; Sylvia, Ike; Mardhiah, Desy (Jurnal The Messenger, 2018)
The use of social media, especially by political figures, can directly bridge communications between politicians and their constituents and other supportive or opposing parties. This study aims to analyze the posts of political figures social media using discourse analysis to convey explicit or implicit messages that can not be separated from political intentions. Discourse analysis helps to understand the meaning of message or text of the media regarding the messenger's social environment and relationships. The study found that three political figures with most followers in three most popular social media platforms--Facebook, Instagram, and Twitter--Prabowo Subianto, Ridwan Kamil, and Susilo Bambang Yudhoyono represent their nationalism and Islamic identity in their social media posts. They also convey their opinions about the general political issues in spite of divisive political condition among public that is also visible among politicians.